PENGARUH WAKTU PENYIMPANAN DAN VARIASI KEMASAN TERHADAP NILAI SUHU DAN KUALITAS FISIK SAWI - Indreswari, Meilody; Nafiusokhib, Nafiusokhib; Ahmad, Salman (EduFisika: Jurnal Pendidikan Fisika, 2021)
The treatment and packaging of wet vegetables such as mustard greens during the delivery process from farmers to consumers greatly affects the quality of mustard greens. In order for mustard greens to last longer, the right material is needed as a packaging medium for mustard greens. Good packaging for vegetables instead of plastic is banana leaves and teak leaves. In this study, we compared packaging with banana leaves, teak leaves and without packaging. Packaging treatment in the cardboard and outside the cardboard. The results showed that mustard greens treated in cardboard boxes with banana leaves decomposed within 7 days, teak leaves 5 days while without packaging for 4 days. The final temperature was 30.5 oC in the teak and banana leaf packages, while the unpackaged temperature was 29.5 oC. Mustard greens treated outside the cardboard box with banana leaf packaging decomposed within 6 days, teak leaves 4 days and without packaging only 3 days. The final temperature was 29.5 oC for banana leaves and teak leaves while those without packaging were 28.5 oC. From the results obtained, the treatment in cardboard and using banana leaf packaging has a long spoilage age.